Assessment of Serum Vitamin D Levels in Women with Polycystic Ovary Syndrome - Hamdi, Rana A.; Abdul-Qahar, Zina H.; Kadhum, Ekhlas J.; Alsaeed, Fatin A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Polycystic ovary syndrome (PCOS) is a common endocrinopathy in women ofreproductive age with primary features of infertility, menstrual irregularity, and clinical or biochemicalevidence of hyperandrogenism (hirsutism, acne and high androgen level). Vitamin D has a role in thedevelopment of metabolic and endocrine abnormalities in PCOS mediated by insulin resistance.Objective: Measure serum 25-hydroxy vitamin D levels in women with polycystic ovary syndrome andcompare their levels with age and body mass index matched healthy controls. Also, assess thecorrelation between insulin resistance and 25-hydroxy vitamin D among women with PCOS.Subjects and Methods: Eighty eight women were involved in this study with age range (18-34 years).Subjects were divided into two groups: Group 1- forty five women with PCOS and Group 2- forty threewomen without PCOS (as controls).Serum 25-hydroxy vitamin D, insulin, free testosterone, Luteinizing hormone (LH), Follicle stimulatinghormone (FSH) were measured by enzyme linked immunosorbent assay (ELISA), while serum calciumand fasting serum glucose were measured by spectrophotometer.Results: Significant increase in mean value of fasting serum glucose, insulin, homeostatic modelassessment of insulin resistance (HOMA-IR), LH, LH/FSH ratio, and free testosterone with significantdecrease in mean value of serum FSH, 25-hydroxy vitamin D, and calcium for patients with PCOScomparing to age and body mass index match controls. Additionally, significant negative correlationswere found between serum 25-hydroxy vitamin D levels with fasting serum glucose (r= -0.484, p=0.01),fasting serum insulin (r= -0.422, p=0.04), and HOMA-IR (r= -0.542, p=0.0001) in women with PCOS.Conclusion: Vitamin D has a role in metabolic and hormonal disturbance seen in PCOS through impactof vitamin D on insulin releasing and function.